ANALISIS PARTISIPASI ANGGOTA PADA KOPERASI SISWA DI SMK NEGERI 3 PONTIANAK - Gustriansyah, Edy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract A cooperative is a business entity that collectively owned and operated in the field of economy, comprising voluntary membership and on the basis of equality of rights and is obligated toconduct a business aimed to providing members' needs and welfare. The ideal and constitutional basis of a school cooperative is Pancasila and the 1945 Constitution. The method was descriptive method, with the form of qualitative research. Referring to the participation by members of the Student Cooperative at SMK Negeri 3 Pontianak based on the participation aspect of the members including capital, utilization of cooperative services, and on the part of expressing opinions in meetings or forums involving members. In this section of research focused on matters relating to the participation of the implementation of the contributions payment by members that experienced an increase of Rp 11,132,450, - or by 85%. Utilization of shopping units provided by cooperatives can be seen from their income statement in the period of 2013 and 2014 in the income column with the increasing percentage as big as 132% and also the involvement of members in expressing their opinions in meetings organized by the board such as Semester Meetings and Year End Meetings. Keywords: Member participation, Economic Resources, Services, & Decision Making